The effect of social network sites on international students' acculturation, adaptation, and wellbeing - Hofhuis, Joep; van Egmond, Marieke C.; Lutz, Franziska E.; von Reventlow, Karin; Rohmann, Anette (Frontiers in Communication, 2023)
A growing body of literature focuses on the impact of social media on well-being of international students. What remains understudied, is how these effects may be explained through acculturation and adaptation processes. This paper examines the mediating roles of acculturation dimensions (cultural maintenance and host country participation) and (psychological and sociocultural) adaptation, on the relationship between host and home Social Network Site (SNS) use and well-being, among two populations: a diverse group of international students in the Netherlands (n = 147) and a sample of Chinese students in Germany (n = 102). The results of both studies show that international students use SNS to initiate contact with the host society, which relates positively to adaptation. However, using SNS to stay in contact with the home culture appears to inhibit the adaptation process, which relates to lower well-being. Our work suggests that these processes are similar across different contexts.